2009
DOI: 10.1007/s00216-009-2806-9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of illicit substances in fingerprints by infrared spectral imaging

Abstract: FTIR and Raman spectral imaging can be used to simultaneously image a latent fingerprint and detect exogenous substances deposited within it. These substances might include drugs of abuse or traces of explosives or gunshot residue. In this work, spectral searching algorithms were tested for their efficacy in finding targeted substances deposited within fingerprints. "Reverse" library searching, where a large number of possibly poor-quality spectra from a spectral image are searched against a small number of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 43 publications
0
50
0
6
Order By: Relevance
“…[10] Very interesting methodologies have been tested for establishing criminal evidence. Ng et al [11] and Chen et al [12] have proposed the infrared spectral imaging detection of illicit substances (such as explosives). It has also been possible to determine residues of explosives after explosion events.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Very interesting methodologies have been tested for establishing criminal evidence. Ng et al [11] and Chen et al [12] have proposed the infrared spectral imaging detection of illicit substances (such as explosives). It has also been possible to determine residues of explosives after explosion events.…”
Section: Introductionmentioning
confidence: 99%
“…This pre-processing corrects broad baseline features and allows overlapping peaks to be resolved because 2nd derivative peaks are always narrower than the original spectral peaks [40,66]. The 2nd Savitzky-Golay derivative was thus systematically applied on each spectrum before any other calculations.…”
Section: Data Pre-processingmentioning
confidence: 99%
“…This study also noted no significant variation in the lipid composition as a function of gender. Numerous studies have also been conducted to determine the ability of FTIR to analyse and identify extrinsic fingermark compounds, such as explosive residue [38][39][40]42,47], drugs [32,56] and other substances [36,47,56,57]. In the area of fingermark aging, only a few studies have been conducted using m-FTIR.…”
Section: Introductionmentioning
confidence: 99%
“…Bhargava et al have reported the use of reflection-absorption mode for the distinction of overlapping fingerprints based on differences in their chemical origins [60]. FTIR imaging has been used to detect exogenous trace residues associated with forensic evidence, e.g., explosives [60][61][62] and illegal substances [63].…”
Section: Vibrational Spectroscopic Imagingmentioning
confidence: 99%